2021
DOI: 10.1186/s40850-021-00096-4
|View full text |Cite
|
Sign up to set email alerts
|

Chamelea gallina reproductive biology and Minimum Conservation Reference Size: implications for fishery management in the Adriatic Sea

Abstract: Background The striped venus clam Chamelea gallina is an economically important species in Adriatic Sea fisheries. The use of hydraulic dredging for its catch has a long history in Italy and its management faced several stages of development in the last 40 years. A great effort has been made in the past two decades to move from poorly or weakly managed fisheries to a well-structured co-management system to improve the sustainability of this fishery. However, a prerequisite for appropriate resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…In a study conducted in the upper Adriatic Sea, Gizzi et al [36] found smaller, macroporous, and less robust shells in organisms exposed to higher solar radiation. In other studies, the same phenomenon was found in organisms exposed to low surface temperatures [37,38].…”
Section: Growth and Reproduction Of Chamelea Gallinasupporting
confidence: 77%
“…In a study conducted in the upper Adriatic Sea, Gizzi et al [36] found smaller, macroporous, and less robust shells in organisms exposed to higher solar radiation. In other studies, the same phenomenon was found in organisms exposed to low surface temperatures [37,38].…”
Section: Growth and Reproduction Of Chamelea Gallinasupporting
confidence: 77%